(untitled) (Revista Direito em Debate, 2021)
The research theme is the analysis of the profile of Brazilian collective law, which presents itself as a contributory factor for the prevention of social damages. The theme has relevance for effective modification of the posture of the Brazilian society and State in face of the dangers and risks detected daily, avoiding serious and irreversible collective damages. Asked in this article if the prioritization of preventive collective protection is an effective mechanism to inhibit and stop the repetition of illegal practices that generate social damages. The theoretical framework used was the neoconstitutionalist approach of the Brazilian constitutional model inaugurated in 1988, which instituted the new summa division between individual and collective rights. It was concluded that there is a need to modify the philosophy and posture of the Brazilian society and State, in order to apply seriously the existing legal systematization, as a mechanism to avoid collective damages, because it does not conform to the Brazilian constitutional model, individualist and patrimonialist performance, as well as posture passive in the face of dangers and risks. The methodology used was the bibliographical revision, with delimitation of the problem through the deductive method, and a historical explanatory analysis of the evolution of State theories and critical interpretative analysis of obstacles to the effectiveness of Brazilian collective law.